Analisis Yuridis Implementasi Pemenuhan Hak Cuti Haid Bagi Pekerja Perempuan Terkait Undang-Undang No. 13 Tahun 2003 - Masning Rhuina, Yaomi Tachyata; Kornelis, Yudi (Ilmu Hukum Prima (IHP), 2024)
This research is a comprehensive examination that seeks to assess the extent to which women workers' rights regarding menstrual leave in Indonesia are fulfilled and protected. Normative legal research was used, and a qualitative analysis approach was employed to address the research problem. A thorough literature review analyzed current conditions, including public awareness, company regulations, legal protections, and implementation challenges. The research findings show that, despite regulations, many companies have not fully optimized the right to menstrual leave in Indonesia. Proper implementation of the Labor Law on the rights of women workers has not been achieved, resulting in injustice, discrimination, and even violence against women workers, hindering legal protection for these workers. Thus, improved policies, increased awareness, and stricter law enforcement are crucial to achieving a work environment supporting women's rights in Indonesia.